Pemanfaatan Media Whatsapp Grouping dalam Peningkatan Kemampuan Bahasa Inggris Ekonomi Mahasiswa Fakultas Ekonomi dan Bisnis - Dewi Surani; AR Chaerudin (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
This study aims to describe the interaction and the quality of WhatsApp Grouping communication, and the use of WhatsApp Grouping in improving the ability of English Economics and Business Faculty Students. This study uses descriptive qualitative research methods, with primary data in the form of semistructured online interviews, participantory observation, documentations. Informants in this study totaled 177 active members of the WhatsApp group from 8 classes. The results showed the majority of informants stated that the interaction and quality of communication on WhatsApp group was good, quality and useful. The existence of WhatsApp Group is useful to support English Economics lectures1, an accurate media of information about lectures for the delivery of material and assignments, task collection, whether in the form of direct comments in chat, pictures / captions, quick dialogue recordings. WhatsApp Grouping has also proven to be beneficial in improving English Economic skills including listening, writing, reading and speaking competencies (listening, writing, reading, speaking). With a series of drilling activities and interactions in groups, students are proven to be more active in English, improve their ability to read, listen, write and improve vocabulary.